The Influence of School-Based Management (MBS) and Transformational Leadership Through Digital Transformation in Improving The Quality of Education at Islamic Boarding School Cirebon SMP - Huda, Muhamad Khozinul; Gofur, Abdul; Mutmainah, Mutmainah; Permatasari, Tria Astika Endah; Bahri, Saiful; Suradika, Agus; Nora, Liza (Raudhah Publisher, 2025)
Quality education is a key factor in enhancing a nation's competitiveness in the era of globalization. Along with the development of time, digitalization in education has become an urgent necessity to improve the effectiveness of learning and school management. School-Based Management (SBM) and transformational leadership are two main factors in improving education quality; however, their effectiveness in addressing the challenges of the digital era remains a subject of debate. This study aims to analyze the influence of School-Based Management (SBM) and Transformational Leadership through Digital Transformation on Education Quality at SMP IBS Cirebon. The research method used is quantitative with a Structural Equation Modeling (SEM) approach to examine the relationships between variables. The results of the study indicate that SBM and transformational leadership (p-value = 0.016) significantly affect education quality (p-value = 0.019). However, both SBM (p-value = 0.000) and transformational leadership (p-value = 0.002) were found to have a significant impact on digital transformation. Furthermore, digital transformation significantly influences education quality (p-value = 0.000) and also acts as a mediating variable that strengthens the relationship between SBM and transformational leadership with education quality. The findings of this study confirm that digital transformation plays a crucial role in enhancing education quality in the modern era. Therefore, schools need to optimize digitalization in management and learning to achieve better education quality.